British policy in Persia, 1918-1925 - Sabahi, Houshang (F. Cass, 1990)
Viewed from the perspective of Whitehall, Persia was a crossroadswhere Britain's European and Indian interests met. Control of Persiaby any European power was bound to jeopardize the security ofBritish India. A threat to India could in turn be used as a lever toupset the balance of power in Europe. To forestall this danger, Britaintried various policies. At first London and India hesitantlyexperimented with the policy of bringing Persia into the Britishsphere of influence either by contracting an alliance with her or byturning her into a protectorate. Persia's crushing defeat in the warwith Ru.